Faktor yang mempengaruhi kejadian dekompresi pada nelayan penyelam tradisional di Pulau Barrang Lompo - Mansur Sididi; Een Kurnaesih; Andi Nurlinda (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: Diving work has a very high level of risk of danger, such as the ease with which divers experience decompression events which can result in paralysis and even death.Objective: This study aims to analyze the factors that influence the incidence of decompression in traditional diver fishermen on Barrang Lompo Island.Methods: This study used a cross sectional study design with a population of 311 people and a total sample of 76 people based on the slovin formula. Sampling using purposive sampling technique. Analyze data using chi square test Results: The results showed that there was no effect smoking behavior (p value = 0.335) and way of rising to the surface (p value = 0.363) and there was an effect of a history of comorbid hypertension (p value = 0.029) on the incidence of decompression in traditional diver fishermen in Barrang Lompo Island. Conclusion : there is no effect of smoking behavior and way of rising to the surface and there is an effect of a history of comorbid hypertension on the incidence of decompression in traditional diver fishermen in Barrang Lompo Island.